Towards a Clearer Understanding of Strategic Awareness : A Conceptual And Empirical Exploration - Haavisto, Eveliina (My University, 2026)
Businesses are constantly faced with challenges caused by the turbulent and unpredictable environment, and they need to work hard in order to stay competitive. As a result, businesses are desperate to find new ways to manage the challenges that are thrown at them. Strategic awareness have gained attention in light of the turbulent environment as a management tool for survival. However, while strategic awareness is considered crucial for businesses survival, the concept of strategic awareness is still overlooked by many and lack a unified understanding. Due to the limited research on strategic awareness and the scattered views on the concept. This study explores what strategic awareness is and how it can be applied in practise and aims to create a clarified understanding of strategic awareness and its practise. It’s examined through a comprehensive literature review of the existing literature, comparing author’s perspectives on the concept, which is synthesized into a conceptual framework. A qualitative study is conducted based on the conceptual framework, with the aim of gaining meaningful insights of strategic awareness and its application in practise in a real-life setting. The data was collected through four semi-structured interviews of individuals with experience in strategic decision making. The data was thematically analysed, and the empirical findings were compared to the conceptual framework developed based on the literature review. A clarified understanding of strategic awareness was found, and key dimensions and elements of the concept was identified. A conceptual framework was developed which reflects both theoretically grounded and empirically informed perspectives, which provide a comprehensive understanding of the concept of strategic awareness and how it can be applied in practise. A key finding of the research was that alignment of views on pursued strategy had a greater part and importance, than understood in the literature review. Suggesting alignment of views to be a key dimension of strategic awareness, along with internal and external environmental awareness. It was found strategic awareness to be essential for businesses to stay competitive and for making informed decision, as well as for a successful implementation of strategy. As strategic awareness was found to help guide actions and decisions of individuals within a business.
Keywords: fi=Taloustiede|en=Economics|; Master’s Programme in Strategic Business Development